IMPLEMENTATION OF REUSE IN THE AGILE SOFTWARE DEVELOPMENT PROCESS SCRUM - R, Jayasudha; V, Viswanathan; P, Shanthi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
The concept of reuse is applied in one of the agile development methodologies called the scrum. Sprint is a single functionality and the result at the end of the sprint functionality is derived as the shippable or bugs. This paper makes an attempt to use the concept of reuse in the agile software development to meet the dynamic change of customer requirements in banks. A banking project is created using both waterfall model and scrum model, and the knowledge gained is stored in the ontology-based repository for the first time. Again, the same project is created for different vendors using the ontology-based repository. The result shows that maximum sprint is reused and all the knowledge gained is stored in the form of ontology. This ontology helps identify the shippable component of each sprint which is a small executable functionality. This leads to less cost and time to deliver the product. The main aim is to increase the availability of the reusable artifacts, which lead to increase the reusability of the developer. The experimental results show improvements in the performance of retrieving the components for the software development. Â Â